Leerexvision : coming people. - Hoet, Jan; Herforder Radewig, Herford ([s.l.] : Herforder Radewig, 2004)
Gröning, Julia ; Kabisch, Heike ; Zint, Manuel ; Lee, Woo Il ; Lounge, Marta ; Brodnicki, Gregor ; Märker, Andreas ; Schigal, Olga ; Roeb, Yvonne ; Heck, Kati ; et al.
Leerexvision: coming people, Herforder Radewig, Herford, vom 04. November bis 19. Dezember 2004
kunstcatalogus